Development of operational modal analysis techniques in wind tunnel environment for a cantilevered composite wing model - Che Saffry, Zetty Azleen (2015)
Identification of modal parameters is crucial especially in aerospace applications whereby the interactions of airflow with aircraft structures can result in undesirable structural deformations. This structural deformation can be predicted with knowledge of the modal parameters. This can be achieved through conventional modal testing that requires a known excitation force in order to extract these dynamic properties. One particular challenge using this technique is that it can be experimentally complex because of the need for artificial excitation and it also does not represent actual operational condition likewise external disturbance loads, e.g instruments and surrounding noise, aerodynamic loads and turbulence. Therefore, a good understanding of the dynamic properties and application of the technique to implement this experimental work needs to be generated. Basic approach is to conduct Ground Vibration Testing (GVT) and use the modal data to determine the flutter onset. The unknown sources or dynamic excitation can be difficult to be applied using the conventional testing. As the industry has expanded with implementation of modal testing, there is a need to have different technique applied which convenient and easy to use. So this is where technique such as Operational Modal Analysis has its application in the field. Not just that, the opportunities of using hybrid composite material can be an attractive prospect for aerospace application. This study utilize Operational Modal Analysis (OMA) on extracting the modal properties. Operational Modal Analysis acquires information about the dynamic characteristics of a structure in terms of natural frequencies, damping and mode shapes without the need for explicit measurement of input vibration inducing loads. This technique is yet to be applied on composite structures in the subsonic range within a wind tunnel environment. Therefore in the current work, it was implemented and demonstrated on a cantilevered hybrid composite plate and wing model exposed to low speed airflow in a wind tunnel. To do so, a single contactless sensing system via a laser vibrometer as well as an accelerometer as reference was employed to measure the vibration response in subsonic speed. Experimental Modal Analysis (EMA) and computational analysis using Finite Element Analysis (FEA) were also conducted as baseline reference. Results from the extensive experimental works had successfully shown that OMA can be implemented in subsonic range on both models and provide modal data with some level of accuracy. From the experiment testing, the testing technique and data handling as well as the aerodynamics effects from the airflow play a major role in affecting the modal parameters. For composite thin plate model, the structure is too light which may affects the modal data. As for wing model which has a stiffer structure, the mode shape for some modes were classified as unidentified as these modes displayed combination of bending and torsional modes, which may indicate coupling of these two modes due to aeroelastic effects. Due to the same reason, the frequencies of the modes extracted are found either decrease or increase with air speed especially on merging modes that will lead to flutter.